Photocatalytic degradation of oxytetracycline hydrochloride pollutants in marine aquaculture wastewater under visible light. Issue 14 (6th December 2019) - Liu, Jinghua; Yu, Xiaocai; Wang, Liping; Guo, Meicen; Tian, Siyao; Zhu, Wanting
Abstract: A CuO/ZnO nanocomposite for use as photocatalyst was successfully prepared by co-precipitation method. Its chemical and physical properties were evaluated by X-ray diffractometry, scanning electron microscopy, EDS, UV–vis diffuse reflectance spectroscopy and photoluminescence spectroscopy. The average particle size of CuO/ZnO composite was found to be around 80 nm. The degradation of oxytetracycline hydrochloride pollutants in marine aquaculture wastewater using ZnO and CuO/ZnO was compared. CuO/ZnO nanocomposite was found to be more efficient than ZnO. The effects of external factors on the photocatalytic efficiency of the nanocomposite were investigated under visible light. Moreover, conditions for the degradation of oxytetracycline hydrochloride using CuO/ZnO nanocomposite were optimized. Based on both, the ability and efficiency of degradation, 10:1 molar ratio of Zn 2+ /Cu 2+ and 0.4 g L –1 nanocomposite, were found to be optimal, using which the average photocatalytic degradation rate of oxytetracycline hydrochloride reached 90%.